Effect of a transcriptional inactive or absent vitamin D receptor on beta-cell function and glucose homeostasis in mice. Issue 164 (November 2016) - Vangoitsenhoven, Roman; Wolden-Kirk, Heidi; Lemaire, Katleen; Verstuyf, Annemieke; Verlinden, Lieve; Yamamoto, Yoko; Kato, Shigeaki; Van Lommel, Leentje; Schuit, Frans; Van der Schueren, Bart; Mathieu, Chantal; Overbergh, Lut
Highlights: Mice with a mutation in the transcriptional activation site of Vdr (VDRΔAF2) were generated. VDRΔAF2 mice have normal fur phenotype but lower body weight than wild type (WT) mice. In vivo glucose tolerance is similar between adult normocalcemic WT, VDR −/− and VDRΔAF2 mice. Ex vivo glucose stimulated insulin secretion is similar in islets from WT, VDR −/− and VDRΔAF2 mice. Phosphodiesterase 10a mRNA is upregulated in VDR −/− and VDRΔAF2 islets, as compared to WT mice Abstract: Vitamin D deficiency is associated with beta-cell dysfunction and a higher risk of diabetes, but mice and humans with an absence of the vitamin D receptor (VDR) display normal glucose tolerance. Here, we investigated the direct effects of absence of VDR or absence of ligand activation of VDR on beta-cell function. For this purpose, we generated mice, with a mutation in the AF2 domain of Vdr (VDRΔAF2), preventing ligand-driven transcriptional activation of vitamin D responsive genes. VDRΔAF2 mice were compared to Vdr full knockout (VDR −/− ) and wild type (WT) mice. In order to avoid hypocalcemia, which has a direct effect on beta-cell function, mice were fed a high calcium, high lactose diet yielding comparable serum calcium in all mice. While VDR −/− mice developed extensive alopecia by the age of 24 weeks, the fur of VDRΔAF2 remained normal. All VDRΔAF2 mice weighed significantly less than WT, while male but not female VDR −/− mice had a lower body weight than WT mice. Dual-energy X-ray absorptiometry showed that both VDRΔAF2 (17.2% (females) and 16.6% (males)) and VDR −/− (15.7% and 14.8%) mice have a lower percentage of body fat (vs 19.3% and 22.2% in WT). Serum 25(OH)D3 concentrations were lower for both VDRΔAF2 (−4.55 fold, P < 0.001) and VDR −/− (−3.7 fold, P < 0.001) as compared to 12 week old WT mice, while serum 1, 25(OH)2 D3 was increased for both strains 94.5 fold (P < 0.01) and 92.8 fold (P < 0.001) for VDRΔAF2 and VDR −/− vs WT, respectively). In vivo glucose tolerance tests performed at 12 and 24 weeks of age, as well as ex vivo glucose stimulated insulin secretion on freshly isolated islets, revealed no major differences between the three strains. Microarray analysis on freshly isolated islets showed only 1 differentially expressed gene, phosphodiesterase 10a ( Pde10a ), which was 2.16 and 1.75 fold up-regulated in VDRΔAF2 and VDR −/− islets as compared to WT islets, respectively (P ≤ 0.001). We conclude that in the presence of normocalcemia, absence of VDR or its ligand-activated transcription of genes has no direct regulatory effect on murine glucose homeostasis or gene expression in islets of Langerhans.